The contribution of personnel to the overall energy intensity of large mining enterprises - Cherevatskyi, D.; Smirnov, R.; Bojko, O.; Bash, V. (Економічний вісник Донбасу, 2024)
The muscle power of a company's personnel, when compared to the total energy expenditure, corresponds to the level of engineering error, which has led to the complete rejection of this factor in practice. In this article, the general function of energy consumption by the enterprise is considered to be the sum of technological sector costs and the energy costs of personnel. Three norms of energy consumption of human labor are applied: physical, economic using macroeconomic indicators, and economic of an institutional nature. The main goal of our study is to assess the energy costs of human labor using various approaches and to test the statistical significance of the impact of the obtained results on the overall energy intensity of a given enterprise. Using the method of the Box-Wilson multifactorial experiment, a study of the influence of factors on the total consumption of energy resources was carried out. It is proven that labor costs in the energy aspect, even when measured by the physical method, have a statistically significant effect. The physical method should be recommended as the primary approach for industrial enterprises. Underestimation of the energy parameters of living labor creates the risk of irresponsible consumption and production. Потужність м’язів персоналу підприємства у порівнянні із загальними енерговитратами відповідає рівню інженерної помилки, що призвело до повної відмови від цього фактору на практиці. У цій статті загальна функція енергоспоживання підприємства розглядається як сума витрат технологічного сектора та енерговитрат персоналу. Застосовуються три норми енергоємності людської праці: фізична, економічна з використанням макроекономічних показників та економічна інституціонального характеру. Основною метою нашого дослідження є оцінка енерговитрат людської праці за допомогою різних підходів та перевірка статистичної значущості впливу отриманих результатів на загальну енергоємність підприємства. За допомогою методу багатофакторного експерименту Бокса-Вілсона проведено дослідження впливу факторів на сумарне споживання енергоресурсів. Доведено, що витрати праці в енергетичному аспекті, навіть виміряні фізичним методом, мають статистично значущий ефект. Фізичний метод слід рекомендувати як основний підхід для промислових підприємств. Недооцінка енергетичних параметрів живої праці створює ризик безвідповідального споживання і виробництва.